2022
DOI: 10.1039/d2fo02257e
|View full text |Cite
|
Sign up to set email alerts
|

Artemisia sphaerocephala Krasch polysaccharide promotes adipose thermogenesis and decreases obesity by shaping the gut microbiota

Abstract: This study was designed to investigate the underlying mechanism of Artemisia sphaerocephala Krasch polysaccharide (ASKP) against obesity. Here, our results showed that ASKP considerably reduced body weight gain and metabolic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Several studies have evidenced that disturbance of host gut microbiota is a vital factor in obesity as well as other diseases. , The 16S rRNA gene sequencing technology was used to explore the regulatory effect of Se-GTP on gut microbiota. As shown in the Venn diagram (Figure A), 233 cases of ASV were detected in the five groups, and the specific ASV numbers of the NC group, HFD group, and three Se-GTP intervention groups were 482, 162, 205, 219, and 370, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have evidenced that disturbance of host gut microbiota is a vital factor in obesity as well as other diseases. , The 16S rRNA gene sequencing technology was used to explore the regulatory effect of Se-GTP on gut microbiota. As shown in the Venn diagram (Figure A), 233 cases of ASV were detected in the five groups, and the specific ASV numbers of the NC group, HFD group, and three Se-GTP intervention groups were 482, 162, 205, 219, and 370, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Obesity is the basis of some chronic diseases, which develops owing to various factors, such as diet, gene, lifestyle, intestinal microbiota, and unbalanced energy metabolism. Recent studies suggest that increasing energy expenditure is a valid approach to treat obesity, among which boosting adaptive BAT thermogenesis and WAT browning have the potential to be the most attractive strategy for treating obesity and related metabolic disorders. , Indeed, our previous study has shown that the use of Artemisia sphaerocephala Krasch polysaccharide, which can promote BAT thermogenesis, could improve metabolic disorders in the obese model . In this study, by integrating data on gut microbiota and BAT, we proved that Se-GTP contributed to a shift in the gut microbiota composition, which stimulated WAT browning, promoted BAT thermogenesis, and subsequently ameliorated HFD causing obesity and related complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations